The impact of digital transformation on the efficiency of administrative processes in government institutions (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aims to analyze the impact of digital transformation on the efficiency of administrative processes in government institutions. It reviews the fundamental concepts of digital transformation and administrative efficiency, and identifies the relationship between them in light of modern applications. The study employs a descriptive-analytical approach, drawing on a review of recent scientific literature and relevant field studies. It concludes that digital transformation effectively contributes to improving the speed of administrative performance, reducing human error, enhancing internal coordination among departments, and improving service quality and increasing citizen satisfaction. The study also identifies several challenges hindering the full implementation of digital transformation, such as resistance to change and a weak digital literacy. It recommends the adoption of integrated digital policies, infrastructure development, and the activation of artificial intelligence tools to support administrative decision-making.
Keywords: Digital Transformation; Administrative Efficiency; Government Institutions; Automation; Artificial Intelligence; E-Services; Administrative Coordination; Institutional Performance; Digital Culture; Governance